Cross-border acquisitions and shareholders' wealth: The case of the Indian pharmaceutical sector - Abdul Wajid; Anjim Sabiha; Shakeb Akhtar; Mosab I. Tabash; Linda Nalini Daniel (Journal of Risk and Financial Management, 2022)
Cross-border acquisitions by Indian companies have increased tremendously, especially during the last two decades, and the pharmaceutical industry is one of the top acquiring industries. This study verifies the relationship between cross-border acquisitions and shareholders' wealth in the Indian pharmaceutical sector. For this purpose, the data related to acquisitions were acquired from 2005 to 2019 and the event study methodology was applied along with two parametric tests. The findings of the current research prescribe that cross-border acquisitions have a positive and significant impact on shareholders' wealth. Furthermore, the outcomes also indicate higher positive abnormal returns in the short run when the targets are based in the US and the UK as compared to the positive but insignificant abnormal returns when the targets are based in locations other than the US and the UK.
Keywords: C58; G34; G14; 650; pharmaceutical firms; cross-border acquisitions; mergers and acquisitions; abnormal returns; event study methodology; short term gains; India